2020
DOI: 10.1038/s41598-020-67431-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the StoRM cohort reveals physical activity to be associated with survival in metastatic breast cancer

Abstract: Benefits of physical activity are widely demonstrated for early stage cancers but few studies have focused on metastatic disease. the purpose of this study was to determine the impact of physical activity on survival in patients with metastatic breast cancer. We conducted a secondary analysis of the national, multicentric, non-randomized, prospective cohort SNPs to Risk of Metastasis (StoRM) study. The level of physical activity was self-reported at inclusion and divided into three categories of physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Total physical activity describes studies that reported on recreational, occupational, transportation and household physical activities combined. We restricted our review to studies that assessed physical activity postdiagnosis and we therefore excluded studies that reported only on prediagnosis physical activity 25‐42 and studies that likely reflected a combination of pre‐ and postdiagnosis physical activity 43‐45 . If a study reported data separately for pre‐ and postdiagnosis physical activity, we included it and used the estimate for postdiagnosis physical activity in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Total physical activity describes studies that reported on recreational, occupational, transportation and household physical activities combined. We restricted our review to studies that assessed physical activity postdiagnosis and we therefore excluded studies that reported only on prediagnosis physical activity 25‐42 and studies that likely reflected a combination of pre‐ and postdiagnosis physical activity 43‐45 . If a study reported data separately for pre‐ and postdiagnosis physical activity, we included it and used the estimate for postdiagnosis physical activity in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, patients with higher levels of physical activity could be explained by the fact that they have better physical functioning and less symptom burden, and thus they are more active and could potentially have a longer survival duration. This assumption is supported by the findings of two included non-RCTs studies that higher proportion of patients with better performance status were reported in more physically active ones [ 33 , 34 ]. Other limitations for observational studies include the possible risk of residual confounding factors that make it difficult to elucidate the real relationship between physical activity and overall survival.…”
Section: Discussionmentioning
confidence: 66%
“…Reporting of advanced stages of disease varied, with six studies defining the sample as advanced cancer by stage (IIIB/IV) [ 26 , 27 , 30 , 35 , 38 , 39 ]. Four studies described the sample as having advanced cancer patients [ 28 , 31 , 34 , 37 ], three studies characterized the sample as advanced based on their described pathologies [ 29 , 32 , 33 ], and one study by the palliative care treatment the patients received [ 36 ]. Six of the studies focused on multiple cancer sites [ 26 , 28 31 , 36 ], four on lung cancer [ 27 , 35 , 37 , 39 ], two on colorectal cancer [ 32 , 34 ], and breast cancer [ 33 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em sua revisão, Knols et al 29 demonstraram que os efeitos positivos da terapia com exercícios variam dependendo do tipo e do estágio de tumor, da terapia farmacêutica, dos procedimentos terapêuticos e do estilo de vida do paciente. Em seu estudo, Delrieu et al 30 consideraram que uma quantidade moderada ou vigorosa de exercício físico permaneceu estatisticamente associada a uma melhor sobrevida global apenas para pacientes com câncer de mama metastático HER2-positivo. Por outro lado, a sobrevida de pacientes com câncer luminal e triplo-negativo não foi afetada pelo nível de exercício físico.…”
Section: Discussionunclassified